Manganese-enhanced MR imaging of brain activation evoked by noxious peripheral electrical stimulation. (2nd February 2016) - Cha, Myeounghoon; Lee, Kyuhong; Lee, Chulhyun; Cho, Jee-Hyun; Cheong, Chaejoon; Sohn, Jin-Hun; Lee, Bae Hwan
Highlights: Mn 2+ -enhanced signals were observed in specific ROIs after peripheral stimulation. The ROIs were highly associated with noxious stimulation. MEMRI could delineate the functional areas of pain perception. Abstract: As imaging technology develops, magnetic resonance imaging (MRI) has furthered our understanding of brain function by clarifying the anatomical structure and generating functional imaging data related to information processing in pain conditions. Recent studies have reported that manganese (Mn 2+ )-enhanced MRI (MEMRI) provides valuable information about the functions of the central nervous system. The aim of this study was to identify specific brain regions activated during noxious electric stimulation using high-resolution MEMRI. Male Sprague Dawley rats were divided into three groups: naïve, sham electrical stimulation, and noxious electric stimulation. Under urethane with α-chloralose mixture anesthesia, a catheter was placed in the external carotid artery to administrate 20% mannitol and manganese chloride (25 mM MnCl2 ). Noxious electric stimulation (2 Hz, 10 V) was applied to the hind paw with a needle electrode. Stimulation-induced neuronal activation was detected using 4.7-T MRI. In response to noxious electrical stimulation, remarkable Mn 2+ -enhanced signals were observed in the agranular insular cortex, auditory cortex, primary somatosensory cortex of the hind limb, and granular and dysgranular insular cortex, which correspond to sensory tactile electric stimulus to the hindpaws. These results indicate that the combination of MEMRI with activity-induced Mn 2+ -dependent contrast can delineate functional areas in the rat brain.